2018
DOI: 10.1186/s12887-018-0998-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between muscle strength and dyslipidemia, serum 25(OH)D, and weight status among diverse schoolchildren: a cross-sectional analysis

Abstract: BackgroundThe relationship between muscle strength and cardiometabolic risk factors in youth, and the potential influence of vitamin D status on this relationship, is not well understood. This study examined associations between muscle strength and dyslipidemia, serum 25-hydroxyvitamin D [25(OH)D], and weight status in diverse schoolchildren.MethodsMeasures of hand-grip strength (standardized for sex and body weight), anthropometrics (height and weight converted to BMI z-score [BMIz]), sociodemographics, and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
34
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 40 publications
6
34
0
2
Order By: Relevance
“…After adjustment for BMI, grip strength was no longer associated with HDLC and TG levels. 20) In contrast, our study used relative HGS, a BMI-adjusted index, and the results were statistically signifi-cant. Some previous studies reported that absolute HGS was associated with metabolic syndrome, including abnormal lipid metabolism.…”
Section: Discussionmentioning
confidence: 71%
“…After adjustment for BMI, grip strength was no longer associated with HDLC and TG levels. 20) In contrast, our study used relative HGS, a BMI-adjusted index, and the results were statistically signifi-cant. Some previous studies reported that absolute HGS was associated with metabolic syndrome, including abnormal lipid metabolism.…”
Section: Discussionmentioning
confidence: 71%
“…Although in 1984 Forbes (31) described for the first time a low muscle mass phenotype in obese children, since then very little attention has been paid to its metabolic implications in pediatrics. Only recently, children and adolescents with low muscle mass and strength have been shown to be at increased risk of developing metabolic dysfunction and CVD (18,(32)(33)(34)(35), as previously reported in the adult nonelderly and elderly populations (6). In a large sample of U.S. youth, aged 8-20 years, Kim et al (18) demonstrated an inverse association between RMM and cardiometabolic risk factors.…”
Section: Discussionmentioning
confidence: 73%
“…(24). HDL-C was discovered to be negatively relevant to muscle function improvement (25)(26)(27). According to these ndings, a negative association between the ratio of TG/HDL-C and risk of sarcopenia should be took into account.…”
Section: Discussionmentioning
confidence: 99%